A comparison of embryo culture strategies for women of advanced age with four or fewer available D3 embryos: a single centre retrospective analysis of 556 patients. (27th May 2022) - Chen, Panyu; Li, Tingting; Zhao, Weie; Chen, Youhua; Fang, Cong
Abstract: The purpose of this study was to compare two embryo culture strategies in older women with four or fewer D3 embryos. A total of 556 eligible patients aged >38 years in a single reproductive centre underwent IVF/ICSI leading to the generation of four or fewer D3 embryos from April 2016 to October 2018. Patients whose D3 embryos were all cultured to blastocyst were classified as group A; those in which none of their embryos was cultured to blastocysts were classified as group B. Cumulative biochemical pregnancy rate, clinical pregnancy rate and live birth rate were similar between the two groups ( p = 0.582, 0.426 and 0.546, respectively). Though more embryo transfer cycles were achieved in group B, significantly higher biochemical and clinical pregnancy rate per embryo transfer cycle were found in group A ( p = 0.001 and 0.003). In patients with blastocyst culture, the clinical conditions of those who had a successful outcome were better than those who failed. Blastocyst culture and transfer can significantly increase pregnancy rate per embryo transfer cycle and may be appropriate in some older patients with a good clinical prognosis.